Predictive value of oxidative stress biomarkers in drug‑free patients with schizophrenia and schizo-affective disorder. (November 2020) - Guidara, Wassim; Messedi, Meriam; Naifar, Manel; Maalej, Manel; Grayaa, Sahar; Omri, Sana; Ben Thabet, Jihène; Maalej, Mohamed; Charfi, Nada; Ayadi, Fatma
Highlights: Oxidative stress may contribute to the development of schizophrenia (SZ) and schizoaffective disorder (SAD). We recruited 45 patients with SZ, 21 patients with SAD and 101 healthy controls. Eight typical oxidative stress biomarkers in their fasting blood samples were measured. This study combines four oxidant biomarkers based on the same population to screen for risk factors for SZ and SAD. The identification of the predictive value of selected biomarkers related to oxidative stress (MDA, PC, AOPP and GSH-Px) in drug free patients with SZ and sad should lead to a better identification of the etiological mechanism of SZ or SAD associated with stress and diet. Abstract: Several studies have suggested that oxidative stress may represent one of the primary etiological mechanisms of schizophrenia (SZ) and schizoaffective disorder (SAD) which can be targeted by therapeutic intervention. The present study was conducted over a period of 24 months, between June 2016 and June 2018. All enrolled subjects were Tunisian, forty five drug‑free male patients with SZ (mean age: 37.6 years), twenty one drug‑free male patients with SAD (mean age: 28.8 years) and hundred and one age and gender matched controls (mean age: 34.2 years) were enrolled in the study. Plasma reduced glutathione (GSH) and Total thiols levels were significantly decreased in patients compared to controls (respectively p <0.001; p =0.050). In addition, malondialdehyde (MDA), advanced oxidation protein products (AOPP) and protein carbonyls (PC) concentrations and glutathione peroxidase (GSH-Px) activity were significantly increased in patients compared to controls ( p <0.001; p <0.001; p <0.001 and p =0.003 respectively). The binary logistic regression analysis revealed that MDA, AOPP, PC and GSH-Px could be considered as independent risk factors for SZ and SAD. When using ROC analysis, a remarkable increase in the area under the curve (AUC) with higher sensitivity (Se) and specificity (Sp) for MDA, AOPP, PC and GSH-Px combined markers was observed. The present study indicated that the identification of the predictive value of this four-selected biomarkers related to oxidative stress in drug free patients should lead to a better identification of the etiological mechanism of SZ or SAD.